Discovery of varlaxins, new aeruginosin-type inhibitors of human trypsins - Heinilä, L M P; Jokela, J; Ahmed, M N; Wahlsten, M; Kumar, S; Hrouzek, P; Permi, P; Koistinen, H; Fewer, D P; Sivonen, K (Organic & biomolecular chemistry, 2022)
Low-molecular weight natural products display vast structural diversity and have played a key role in the development of novel therapeutics. Here we report the discovery of novel members of the aeruginosin family of natural products, which we named varlaxins. The chemical structures of varlaxins 1046A and 1022A were determined using a combination of mass spectrometry, analysis of one- and two-dimensional NMR spectra, and HPLC analysis of Marfey's derivatives. These analyses revealed that varlaxins 1046A and 1022A are composed of the following moieties: 2-O-methylglyceric acid 3-O-sulfate, isoleucine, 2-carboxy-6-hydroxyoctahydroindole (Choi), and a terminal arginine derivative. Varlaxins 1046A and 1022A differ in the cyclization of this arginine moiety. Interestingly, an unusual α-D-glucopyranose moiety derivatized with two 4-hydroxyphenylacetic acid residues was bound to Choi, a structure not previously reported for other members of the aeruginosin family. We sequenced the complete genome of Nostoc sp. UHCC 0870 and identified the putative 36 kb varlaxin biosynthetic gene cluster. Bioinformatics analysis confirmed that varlaxins belong to the aeruginosin family of natural products. Varlaxins 1046A and 1022A strongly inhibited the three human trypsin isoenzymes with IC50 of 0.62-3.6 nM and 97-230 nM, respectively, including a prometastatic trypsin-3, which is a therapeutically relevant target in several types of cancer. These results substantially broaden the genetic and chemical diversity of the aeruginosin family and provide evidence that the aeruginosin family is a source of strong inhibitors of human serine proteases.
Keywords: arginin; Arginine; biologické přípravky; vysokoúčinná kapalinová chromatografie; Molecular Structure; molekulární struktura; lidé; Chromatography, High Pressure Liquid; Trypsin; trypsin; Biological Products; Humans